Synthesis and photodynamic properties of amphiphilic A3B- phthalocyanine derivatives bearing N-heterocycles as potential cationic phototherapeutic agents - Tempesti, Tomas Cristian (2011)
Unsymmetrically substituted A3B-phthalocyanine derivatives bearing annulated 6-membered N-heterocycles, pyridine and pyrazine rings, were synthesized by the ring expansion reaction of boron(III) subphthalocyanine chloride. A geometrically constrained subphthalocyanine unit was reacted with a range of 1,2-phthalonitrile derivatives in presence of 8-diazabicyclo[5.4.0] undec-7-ene to form the A3B-phthalocyanine. The reactions were carried out in DMSO/1-chloronaphthalene at 130-140 °C for 15 h. This synthetic strategy resulted in phthalocyanines in 37-42% yield that required only simple purification. Annulated 6-membered N-heterocycles were methylated to obtain cationic Zn(II)phthalocyanine derivatives. The spectroscopic and photodynamic properties of these photosensitizers were studied in N,N-dimethylformamide solution. Antifungal activity photoinduced by these compounds was evaluated in Candida albicans cellular suspensions. The results indicate that amphiphilic cationic phthalocyanines represent interesting agents with potential applications in photodynamic inactivation of microorganisms. © 2011 Elsevier Ltd. All rights reserved.